Role of Oxygen Vacancy Sites on the Temperature-Dependent Photoluminescence of SnO2Nanowires - Choi E. (2021)
This work was supported by the National Research Foundation of President Post-doctoral fellowship Program (NRF-2013R1A6A3A060443). L. De Los Santos Valladares thanks the Incorporacion de Investigadores Program from the CONCYTEC - World Bank - UNMSM (Contrat No. 12 -2019 - FONDECYT - BM - INC. INV.) for supporting his research at the University of San Marcos, Peru.